Koalisi Wacana dalam Debat Pemekaran Papua: Analisis Jaringan Wacana Debat Pemekaran Tiga Provinsi Baru di Papua - Sumirat, Panji Arief; Eriyanto, Eriyanto (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2023)
The ratification of the three Laws (UU) the territorial split of the Papua has sparked debate in various circles. Pros and cons actors convey narratives that contain discourse to influence the public's view of the Papua’s territorial split. This study uses the Discourse Network Analysis (DNA) method to map coalitions of actors and discourses on the territorial split of Papua based on actor arguments in the mass media. The discourse coalition study aims to communicate strategies and policy making in the debate on the territorial splits of Papua. The results of the study show that the cons actors are more heterogeneous than the pro actors who are dominated by the government. The discourse raised by the two groups is related with one another. The historical context used in the discourse relates to problems that have long faced Papua: distribution of development, the distance from government control, social welfare, etc. Mapping of discourse coalitions and actors can be utilized in policy making in political debates. In the plan for the territorial splits of Papua, the government needs to discuss with groups that represent the Papuans.